Federalisasi dan Demokratisasi Indonesia - Samsu Rizal Panggabean (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 1998)
This article, the first of two articles, maintains that federalism is a democratic solution to problems of governance in contemporary Indonesia, despite its present abuse as a term. Four reasons are introduced as to why